Evaluasi Stabilitas dan Pergeseran Secant Pile Pada Pekerjaan Galian Lereng Perbukitan Kabupaten Kebumen - Putra, Paksitya Purnama; Kusuma, Dian Natalia; Wicaksono, Luthfi Amri; Rikarda, Raden Denisio Edwin (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
One of the building constructions on the hillside in Kebumen Regency requires the implementation of a cut and fill process on the natural slope. The excavation work on the 7-meter-deep slope of cohesive soil has been reinforced with a secant pile type retaining wall. However, during the excavation process, the secant pile experienced a displacement of 1.1 meters. Therefore, it is necessary to evaluate the causes of the displacement of the retaining wall. The finite element analysis software, Plaxis, is used to analyze and evaluate based on displacement values and safety factors. Additionally, the Geo5 software is used to design the depth of secant pile retaining walls using the Rankine analysis method. The evaluation of the excavation construction work resulted in a safety factor of 1.3984. This value is still below the value required by SNI 8460:2017. Based on the analysis with the software, it was found that the secant pile diameter of 60 cm could still cause a displacement of 1.1 meters, even though the safety factor remained stable. The displacement of the retaining wall occurred because the excavation process resulted in the active earth pressure being greater than the passive earth pressure. After optimizing the design, the results show that increasing the secant pile diameter can reduce the displacement and improve the safety factor to meet the requirements of SNI 8460:2018, which is ≥ 1.5. The effective diameter obtained in the optimization is 80 cm, which can reduce the displacement to 0.3 meters.